2020
DOI: 10.1590/1413-2311.279.98525
|View full text |Cite
|
Sign up to set email alerts
|

Public-Private Partnerships: Origin, Limitations and Prospects for Public Sector Accounting

Abstract: The main objective of this research is to identify and discuss theoretically the advances, limitations and perspectives pointed by international research to improve the accountability and evaluation aspects of PPPs. This is a theoretical essay based on the Public Choice Theory to show that the PPP accounting treatment is relevant to avoid lack of transparency and accountability, mitigating possible losses in the decision-making process and the ineffective allocation of public resources. The discussion of topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(23 reference statements)
0
1
0
1
Order By: Relevance
“…Successful experience in applying PPPs in different countries has shown that the state can use services of a qualified private sector for effective implementation of development programs that eliminate the weaknesses of the public sector (Azami-Aghdash et al, 2020;Sehgal, Dubey, 2019). Such studies as (Matos, Gonçalves, 2020;Palcic et al, 2019) are the matter of the most interest for the present study: they are devoted to the assessment of transparency and controllability of reducing possible losses related to the decision-making process and inefficient allocation of public resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Successful experience in applying PPPs in different countries has shown that the state can use services of a qualified private sector for effective implementation of development programs that eliminate the weaknesses of the public sector (Azami-Aghdash et al, 2020;Sehgal, Dubey, 2019). Such studies as (Matos, Gonçalves, 2020;Palcic et al, 2019) are the matter of the most interest for the present study: they are devoted to the assessment of transparency and controllability of reducing possible losses related to the decision-making process and inefficient allocation of public resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Na fase pré-contratual, a evolução desses projetos depende de uma série de fatores, que incluem o arcabouço regulatório, a disponibilidade de financiamentos (Périco & Rebelatto, 2005), os fatores políticos e institucionais (Firmino, 2018), a modelagem adequada do projeto e as unidades governamentais de PPP com conhecimentos sólidos (Thamer & Lazzarini, 2015). Esses elementos nem sempre estão presentes no contexto brasileiro, o que exige uma maior clareza contratual no que tange a mecanismos de verificação independente e indicadores de desempenho (Barbosa & Malik, 2015), estruturas de incentivo (dos Reis & Cabral, 2017), a definição mais acurada do nível ótimo de garantias e alocação de riscos (Brandão & Saraiva, 2007) e transparência e controle dos investimentos públicos (Matos & Gonçalves, 2020) . Já em sua fase operacional, esses projetos foram pouco estudados em termos de resultados financeiros, operacionais e sociais.…”
Section: Introductionunclassified